A tribute to Professor Sergio Adamo, Full Professor of Histology and Embryology at Sapienza University, Rome - Bianca Maria Scicchitano; Marina Bouchè; Clara Nervi; Dario Coletti (PAGEPress Publications, 2022)
Sergio Adamo prematurely left us on January 7th 2022, just one year after his retirement, leaving his family, friends and colleagues deeply sad and grieving. Sergio was a full Professor of Histology and Embryology at the Sapienza University of Rome. Since the foundation of the Institute of Histology and Embryology more than 50 years ago, he dedicated himself to the institution, research, and teaching with integrity, generosity, and a great sense of teamwork. Sergio's main research interests have been the mechanisms of myogenesis, muscle homeostasis and regeneration under normal and pathological conditions. Most relevant results obtained by Sergio and his collaborators indicate novel functions for the neurohypophyseal hormones, vasopressin and oxytocin, upon striated muscle differentiation, trophism, and homeostasis. Here we like to give the proper tribute to a mentor, a colleague and a sincere friend. He left an indelible mark on the professional and personal lives of all of us and his absence provokes a profound sense of emptiness.